The Genogram as a Counseling Tool: Philosophical Foundations and Practical Implications - Irmayanti, Rima; Suherman, Uman; Nurihsan, Juntika; Budiman, Nandang (Universitas Negeri Padang, 2024)
Genogram as a tool in the counselling process has a long history and is not just a term, but it is based on a clear philosophical foundation. This study uses a qualitative approach with a literature review method that includes primary articles and books. The results of the study indicate that a genogram is a diagrammatic representation of family conditions and information from several generations, which can explain status, work patterns, lifestyle, illness, gender, and other factors. By understanding the good or bad family history, individuals can use this information to anticipate and prevent future problems and guide them to achieve more positive conditions. The use of a genogram in counselling provides deep insight into hereditary patterns and dynamics, helps clients understand interpersonal relationships, and gives them strength to face life's challenges.